MATLAB for engineers - Moore, Holly (Pearson Education Limited, 2019)
Students reading this text should have an understanding of college-level algebra and basic trigonometry. The text includes brief backgrounds when introducing new subjects like statistics and matrix algebra. Sections on calculus and differential equations are introduced near the end and can be used for additional reading material for students with more advanced mathematical backgrounds.